Evaluating the renewable energy sources in Malaysia - Saeed, Khurram (2015)
Energy consumption has risen in Malaysia because of the developing strategies and increasing rate of population. Depletion of fossil fuel resources, fluctuation in crude oil prices, and emission of new environmental problems due to the greenhouse gases effects of fossil fuel combustion have convinced governments to invest in development of power generation based on renewable energy resources. Recently, power generation from the renewable energy resources has been taken into account in the energy mix of every country to supply the annual electricity demand. The current work will give an overview of the renewable energy sources in Malaysia emphasizing more on the marine renewable energy sources status for Malaysia in terms of the available methods of resource assessment, potentiality and the existing policies that support the utilization of the marine renewable energy as an alternative source of energy. A survey was carried out to analyze the best possible methods for the resource assessment of Marine Renewable Energy as well as the resource potentiality in Malaysia. Based on the survey carried out, it was found that Malaysia has a great potential in Wave Energy and Wind Energy, where the potential for Wave Energy and Wind Energy is found to be approximately 53% and 24% which is significantly a higher number considering the ocean conditions in Malaysia and also the survey result was compared by calculating the power being generated by Wave and Wind in Kuala Terengganu region and it can be projected that Wave and Wind energy has the highest potential as agreed by most of the respondents . The results obtained in this research are significant for the growth of Ocean Renewable Energy in Malaysia if used on a large scale.